The Use of Fuzzy Analytical Network Process Method in Selecting Suppliers by Considering Organizational Management Aspects - Arif Imran; Fadillah Ramadhan; Muhammad Nugroho Nitisastra (Jurnal Rekayasa Sistem & Industri, 2020)
Supplier selection is an important activity in collaborative processes between companies. Manufacturingcompanies must pay attention to all aspects of the supplier and not only look at the aspects inherent to theproduct, but other important aspects such as organizational management aspects. Capability, reputation,and supplier ethics must be considered to maintain consistency of collaboration. Good organizationalmanagement of the supplier company will create a reliable system and have an impact on increasing thecompetitiveness of the manufacturing company or the supplier itself. One of the supplier selectiontechniques that can be used to produce a good solution is the Fuzzy Analytical Network Process (F-ANP)method. This method can produce better quality solutions, where the level of subjectivity and inaccuraciesthat occur can be minimized compared to the usual ANP method. In this study, a manufacturing companythat prioritizes organizational management as an important aspect of supplier collaboration is the researchobject. From the results, a more comprehensive and better supplier priority selection is obtained byconsidering the organizational management criteria.